2011
DOI: 10.1111/j.1540-8191.2010.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Vena Cava Filter Migration to the Right Ventricle

Abstract: Inferior vena cava (IVC) filter placement is recommended for acute proximal deep venous thrombosis if anticoagulation is contraindicated. A 52-year-old man presented with weakness, dyspnea, syncope, and renal failure 8 months after IVC filter placement. Imaging revealed migration of the IVC filter to the right ventricle. Endovascular retrieval was not feasible, thus surgical extraction and tricuspid valve repair was performed. IVC filter migration to the heart is a rare, but a potentially life-threatening comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…All retrievable IVC filters can function as permanent filters if they are not removed. Several studies have indicated that only a small percentage of retrievable IVC filters (2-20 %) are removed and device related complications have been reported [4][5][6][7][8]. Recently the U.S. Food and Drug Administration issued a medical alert to address these considerations and emphasized filter removal as soon as protection from PE is no longer necessary [9].…”
mentioning
confidence: 99%
“…All retrievable IVC filters can function as permanent filters if they are not removed. Several studies have indicated that only a small percentage of retrievable IVC filters (2-20 %) are removed and device related complications have been reported [4][5][6][7][8]. Recently the U.S. Food and Drug Administration issued a medical alert to address these considerations and emphasized filter removal as soon as protection from PE is no longer necessary [9].…”
mentioning
confidence: 99%
“…Rather, they suggested an individualized approach to symptomatic patients. Other percutaneous and surgical approaches have been reported in case reports involving symptomatic and life threatening situations [12] , [13] , [16] , [18] , [19] , [21] , [24] . The use of such interventions in asymptomatic patients hasn't been described well and further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical removal of the OPTEASE IVC filter (Cordis Endovascular, Bridgewater, NJ, USA) with concomitant tricuspid cusp repair [4] or tricuspid valve replacement [2] has been reported. Our case is the first surgical report regarding filter removal for life-threatening ALN filter migration to the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of filter migration, defined as <2-cm displacement from the initial location, is reportedly 1.3% [1]. However, major migration, such as that to the heart, is a rare but life-threatening complication [2][3][4]. We herein report a patient who underwent emergent operation for IVC filter migration to the heart.…”
Section: Introductionmentioning
confidence: 98%